Investment Analysis and Business Scheme for the New Cargo Village in Soekarno-Hatta International Airport - Noor, Achmad Rizal; Sumirat, Erman (The Indonesian Journal of Business Administration, 2012)
Soekarno-Hatta International Airport (SHIA) is the main airport serving the greater Jakarta area. It is the biggest and busiest airport in Indonesia with 52.4 million passengers and over 572 thousand tons of cargo in 2011. With current growth of cargo movement and cargo terminal capacity of 500,000 tons per year, SHIA new cargo terminal development is inevitable. PT Angkasa Pura II (PT AP II) as the company that manages and runs SHIA planned to develop new cargo terminal or cargo village to meet future cargo movement through SHIA. PT AP II interested in becoming Cargo Terminal Operator in SHIA. Existing condition in SHIA cargo terminal and plan for new Cargo Village create opportunity for PT AP II to enter as cargo terminal operator. Before deciding whether to become cargo terminal operator or let other cargo terminal operator as operator in SHIA Cargo Village, PT AP II wanted to know which development scenario – Self-Build & Operations or Build-Operate-Transfer - has the highest financial indicators. Monte Carlo Simulation is conducted to determine the probability of success of each business scheme. Financial Projection and Simulation showed that BOT – Revenue Sharing is the best scenario for PT AP II. Adjustment in revenue sharing scheme can produce better financial indicators for PT AP II and balance the financial indicators between PT AP II and Business Partner. Keywords: investment analysis,monte carlo simulation airport, cargo terminal